Language tone in financial news media and the cross-section of stock returns - Mikael Bask; Lars Forsberg; Andreas Östling (Uppsala University, Department of Economics, 2020)
Based on 58,256 news articles published in the Financial Times during a 15-year period that cover companies in the DJIA, we find that a trading strategy that longs stocks with the most negative news and shorts stocks with the least negative news is not profitable. Consistent with this result, we also find that the sentiment factor derived from the negativism in the language tone in news articles is not a priced risk factor in the cross-section of stock returns. Nevertheless, the sentiment factor is significant for two-thirds of the stocks when it is added to well-known factor models.
urn:nbn:se:uu:diva-409685
Keywords: G01; G11; G12; 330; asset pricing; factor models; Fama-French; news articles; sentiment